2016
DOI: 10.18632/oncotarget.12561
|View full text |Cite
|
Sign up to set email alerts
|

The role of the androgen receptor in ovarian cancer carcinogenesis and its clinical implications

Abstract: Ovarian cancer is the major cause of death in women with gynecologic malignancies. There is emerging evidence that Androgen/androgen receptor (AR) signaling plays a critical role in the etiology and progression of this disease. Androgen receptor is frequently expressed in various subtypes of ovarian cancers and androgen/AR signaling has been shown to promote proliferation, migration, and invasion of ovarian cancer cells. Furthermore, shorter AR CAG repeats length and increased AR activity are associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 63 publications
2
41
0
Order By: Relevance
“…observed that LDL was a significant predictor of poor clinical outcomes, whereas a remarkably significant association between elevated LDL levels and improved RFS was identified in the present study cohort. This could be partly attributed to the involvement of different study participants: while the previous study was limited to patients with stage IIIc/IV epithelial ovarian cancer, the present study involved patients with various subtypes, and in varying clinical stages of, ovarian cancer, and it is well known that there is a substantial variation in risk factors, molecular events, and prognostic markers across subtype in epithelial ovarian cancer . Another feasible explanation is that different cut‐offs were used to determine high and low levels of LDL.…”
Section: Discussionmentioning
confidence: 95%
“…observed that LDL was a significant predictor of poor clinical outcomes, whereas a remarkably significant association between elevated LDL levels and improved RFS was identified in the present study cohort. This could be partly attributed to the involvement of different study participants: while the previous study was limited to patients with stage IIIc/IV epithelial ovarian cancer, the present study involved patients with various subtypes, and in varying clinical stages of, ovarian cancer, and it is well known that there is a substantial variation in risk factors, molecular events, and prognostic markers across subtype in epithelial ovarian cancer . Another feasible explanation is that different cut‐offs were used to determine high and low levels of LDL.…”
Section: Discussionmentioning
confidence: 95%
“…15 A longer polyQ repeats generally impose a reduced AR transactivation activity and decreased risk of ovarian cancer. [16][17][18][19] The data of studies on polyG are limited and controversial, and therefore further investigation is required. 19 There are two independent activation domains in the NTD, including activation function-1 (AF1) and activation function-5 (AF5).…”
Section: The Ntd Domainmentioning
confidence: 99%
“…[16][17][18][19] The data of studies on polyG are limited and controversial, and therefore further investigation is required. 19 There are two independent activation domains in the NTD, including activation function-1 (AF1) and activation function-5 (AF5). With the aid of mutagenesis analysis, Jenster et al 20 identified the two regions (residues 51 to 211 and 244 to 360) present in the NTD essential for the transcriptional activation of AR.…”
Section: The Ntd Domainmentioning
confidence: 99%
“…Previous studies have shown that AR negativity is associated with high-grade tumors, together with the decrease of expression associated with recurrent disease and poor prognosis [23][24][25] . The androgen receptor also decreases after chemotherapy 26 .…”
Section: Discussionmentioning
confidence: 98%